Evaluation of Partial Breast Reirradiation with Intraoperative Radiotherapy after Prior Thoracic Radiation: A Single-Institution Report of Outcomes and Toxicity - Chin, Christine; Jadeja, Priya; Taback, Bret; Horowitz, David P.; Feldman, Sheldon M.; Ha, Richard; Connolly, Eileen P. (Frontiers in Oncology, 2017)
Introduction: Mastectomy is the current standard of care for ipsilateral breast tumor recurrences (IBTR) after prior whole breast irradiation (WBI). We report our single-institution experience with breast-conserving surgery (BCS) followed by intraoperative radiotherapy (IORT) as an alternative to salvage mastectomy for new or recurrent breast cancers that develop in the setting of prior thoracic radiation. Methods: We performed an IRB-approved retrospective review of patients treated with breast IORT between September 2013 and November 2016. We identified 12 patients who declined salvage mastectomy for their breast cancer after prior thoracic radiation. IORT was delivered using the Intrabeam device (Carl Zeiss, Germany). A dose of 20Gy was prescribed to the lumpectomy cavity surface using 50kV X-rays. We graded both acute and late treatment-related breast toxicities using the NCI CTCAE version 4.0. Local control, mastectomy-free survival, distant metastasis and overall survival were determined. Results: Our study included 9 patients who developed a new or recurrent ipsilateral breast cancer after prior WBI for early-stage breast cancer, 2 patients with primary breast cancer after mantle-field radiation for Hodgkin’s lymphoma, and 1 patient with a synchronous stage III non-small cell lung cancer treated with definitive radiation to the ipsilateral lung and mediastinum. The median time from prior radiation to presentation was 18 years (range: 2 months-46 years). All patients successfully underwent partial breast re-irradiation with IORT and were able to preserve their breast. At a median follow-up of 14 months (4-25 months), there were no local or distant recurrences. There was a single non-cancer related death. In the acute setting, we observed grade 1 toxicity in 58% (n=7), grade 2 toxicity in 17% (n=2), and no grade 3 or higher toxicity. In the late setting, at least 3 months after IORT, we observed grade 1 hyperpigmentation and/or fibrosis in 50% (n=6), symptomatic seroma requiring drainage in 33% (n=4). A single patient developed an abscess requiring hospitalization and intravenous antibiotic therapy. Conclusions: BCS with IORT is a feasible salvage option for patients who present with localized breast cancer after prior thoracic radiation treatment. Continued follow-up of these patients is warranted given the incidence of delayed toxicity.